2018
DOI: 10.1159/000485122
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconduction of Unrestricted Somatic Stem Cells on an Electrospun Polylactic-Co-Glycolic Acid Scaffold Coated with Nanohydroxyapatite

Abstract: The limitation of traditional bone grafts could be overcome by applying engineered bone constructs, which are mainly produced by seeding suitable stem cells on appropriate scaffolds. So far, bone marrow-derived stromal cells have been the most applied cells in bone tissue engineering, but current data show that unrestricted somatic stem cells (USSCs) from human cord blood might actually be a better stem cell source due to the accessibility and noninvasive procedure of collection. In this study, we cultured USS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In the area of engineered bone graft, the utilization of a suitable scaffold with a regenerative additive has been described, with each respective component of the construct showing efficacy in the area of bone regeneration. In the case of PLGA scaffold, in vitro studies have demonstrated its osteoconductive properties and ability to maintain space, while preventing unwanted soft tissue infiltration (Shahi et al, ). The efficacy of PLGA material was further validated when, used as membranes in both in vitro and in situ, guided tissue regeneration, with significant bone regeneration (Hoornaert, d'Arros, Heymann, & Layrolle, ; Kawasaki, Ohba, Nakatani, & Asahina, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the area of engineered bone graft, the utilization of a suitable scaffold with a regenerative additive has been described, with each respective component of the construct showing efficacy in the area of bone regeneration. In the case of PLGA scaffold, in vitro studies have demonstrated its osteoconductive properties and ability to maintain space, while preventing unwanted soft tissue infiltration (Shahi et al, ). The efficacy of PLGA material was further validated when, used as membranes in both in vitro and in situ, guided tissue regeneration, with significant bone regeneration (Hoornaert, d'Arros, Heymann, & Layrolle, ; Kawasaki, Ohba, Nakatani, & Asahina, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PLGA can be readily processed and fabricated, thereby increasing the supply of the final polymeric material (Danhier et al, ; Zhao et al, ). These favorable properties, as well as the ability to manufacture the polymer in a filamentous form, has afforded interests to expand the use of PLGA polymer into a biodegradable scaffold for the regeneration of bone (Noronha Oliveira et al, ; Shahi et al, ). Both the United States Food and Drug Administration (USFDA) and European Medicine Agency (EMA) have approved PLGA as a drug delivery vehicle, clinical diagnostic tool, and tissue engineering construct (Lu, Wang, Marin‐Muller, et al, ; Martins, Sousa, Araujo, & Sarmento, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the existence of bioactive SF/HA molecules and the nanofibrous structure, supported biological functions. 21 Shahi et al 22 indicated the improved adhesion and proliferation of USSCs on electrospun PLGA/HA.…”
Section: Introductionmentioning
confidence: 99%
“…Allograft use risks disease transmission and has limited availability from young, healthy donors 39 [De Long et al, 2007;Campana et al, 2014]. Consequently, there is increased interest in tissue-40 engineered bone substitutes [Wanschitz et al, 2007;Pina et al, 2017;Shahi et al, 2018;Iaquinta 41 et al, 2019]. 42…”
Section: Introduction 29mentioning
confidence: 99%